Indicator Measurement and Outcome Reporting Following Short-Term Neurosurgical Mission Trips: A Systematic Review (1960-2020). (16th November 2020) - Penuela, Maria; Jella, Tarun; Mehmood, Amber; Fuller, Anthony; Wright, Christina; Shammassian, Berje Haroutuon
Abstract: INTRODUCTION: Despite recent advances in global health, morbidity and mortality remain high for diseases requiring surgical intervention. In the field of neurosurgery, recent reports suggest over 5 million essential surgical cases, ranging from traumatic brain injuries to tumor resections, go untreated each year and remain disproportionately concentrated in low and middle-income countries (LMIC). Short term neurosurgical missions, typically composed of surgical teams from high-income countries (HIC) volunteering for several weeks or months, are a common strategy to address these disparities. They have not, however, been historically concerned with data collection, long-term sustainability, or local capacity development. METHODS: A systematic search of MEDLINE, EMBASE, Scopus, and OVID was performed using select medical subject heading (MeSH) terms for neurosurgical mission trips to LMICs. All identified abstracts underwent duplicate review with an independent third party to resolve disagreements. The same process was continued for full-text review. Included studies involved empirical data analysis and were available in the English language. Excluded studies lacked empirical data, were unrelated to LMICs, were based in conflict zones, analyzed mobile surgical platforms sent from in-country hospitals, or involved patients transported to HICs for treatment. RESULTS: The primary search returned 154 records, of which 13 were included in the final qualitative synthesis. Among the included studies, publication years ranged from 2007 to 2020, with the majority published after 2010. A diverse geography of missions was observed, with reports from 14 countries spanning four continents. The most commonly measured indicator was complication rates (69%, n = 9), followed by operative mortality (38%, n = 5). Other outcomes reported included follow-up rate (23%, n = 3) and follow-up length (30%, n = 4). No data was reported on impoverishing or catastrophic patient expenditures. CONCLUSION: In the past decade, there has been an increase in empirical data reporting for key indicators and outcomes following short-term neurosurgical mission trips. Future collaborations between the HIC and LMIC surgical workforces should focus resources on capacity development, long-term sustainability, as well as research into impoverishing and catastrophic expenditures.